Redução do risco cardiometabólico em usuários do Sistema Único de Saúde e da Rede Suplementar submetidos à cirurgia bariátrica - Almeida, Rebeca Rocha de (2018)
INTRODUCTION: Obesity is associated with an increased cardiovascular risk factor in all social classes and bariatric surgery (BS) has been widely used to promote weight loss and, consequently, reduce cardiometabolic risk (CR). However, there is a shortage of studies showing the disparity in clinical and nutritional evolution after BS, in users of the Unified Health System (UHS) and the Supplementary Health Network (SHN). OBJECTIVE: To evaluate the behavior of the factors associated to the CR of the patients submitted to BS under UHS and SHN. METHODS: This is an observational longitudinal analytical study performed in patients of both sexes submitted to BS under UHS and SHN. The anthropometric and clinical parameters related to the CR (Diabetes Melittus (DM), dyslipidemia and Systemic Hypertension (SAH)) were evaluated, and quantified using the Obesity-Related Comorbidity Assessment (ACRO) score at the following time points: admission, preoperative and in the postoperative returns (3, 6 and 12 months). Statistical analyzes were performed using the Statistical Package for the Social Science, SPSS®, version 17.0 for Windows, considering at the 5%(p <0.05) level of significance. RESULTS: The mean age of the sample was 39.6 ± 10.8 years, the majority being female (72.1%). At the time of admission to BS, UHS users, compared to SHN, had higher frequencies of severe obesity (p <0.0001), SAH (p = 0.008) and DM (p = 0.018). The time elapsed between initial and pre-surgical evaluation was higher for UHS patients (p <0.0001); and, in this period, there was a reduction of the AORC, at the expense of SAH, only in the SHN group. However, it was observed that the two groups showed a reduction of comorbidities in the postoperative period in such a way that there was no difference between the two in the AORC score of 3, 6 and 12 months of BS. CONCLUSION: In the scope of UHS, BS is performed in patients with a higher degree of comorbidities but, the BS provided a reduction of the CR similar to that observed in SHN.